23.5k views
3 votes
Jamal states that ax + b = a(x + c), given a, b, and c are not equal to 0. What must be the value of c for Jamal's statement to be true?

User Nemani
by
4.8k points

1 Answer

4 votes

ANSWER

For Jamal statement to be true,


c = (b)/(a)

Step-by-step explanation

The given statement is:

ax + b = a(x + c)

We expand the left hand side to obtain,

ax + b = ax + ac

Subtract ax from from both sides of the equation.

b=ac

We know that, a≠0 , so we can divide through by 'a'.


(b)/(a) = c

User DharmaTurtle
by
5.5k points